Pengaruh Kecanggihan Teknologi Informasi dan Pengetahuan Pengguna Terhadap Efektivitas Sistem Informasi Akuntansi : (Studi Kasus pada Koperasi yang ada di Wilayah Cimahi Utara) - Jejen Jaenudin; Nastiti Rizky Shiyammurti (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This research was conducted in cooperatives in the North Cimahi region. The purpose of this study was to examine the effect of sophistication of information technology and management knowledge on the effectiveness of accounting information systems in cooperatives in the North Cimahi region. The population in this study were customers of cooperative management in the North Cimahi region, with a sample of 63 administrators. The sampling technique used was the census sampling method or the saturated sample. The research design used descriptive and associative methods. The results of the descriptive analysis showed that the average score of the information technology sophistication variable (X1) was 196 categorized as "enough", and the management knowledge variable (X2) was 190 categorized as "enough", and the accounting information sistem effectiveness variable (Y) was equal to 198 were categorized as “enough”. For associative analysis using, multiple linear regression analysis. The results of the calculation of the influence of the passive can be seen that the variable sophistication of information technology on the effectiveness of the accounting information system is 14.5% and the knowledge of the management variable is 52.3%. The results of the calculation of the influence of the variable sophistication of information technology and management knowledge on the effectiveness of the accounting information system simultaneously can be seen that the value of R square (R2) is 0.669, then the coefficient of determination (KD) is 0.669 x 100% = 66.9%, this means the effect of sophistication of information technology and management knowledge on the effectiveness of accounting information system effectiveness is 66.9%, while the remaining 33.1% is influenced by other factors not involved in this study.